Multi-Grade Teaching: Its Effect on Teachers and Students’ Performance at Datu Hoffer Ampatuan District (American Journal of Multidisciplinary Research and Innovation, 2025)
Multi-grade teaching is an intrinsic element of school administrators and teachers achieving success in education. In a sample of 40 regular teachers of seven (7) schools of Datu Hoffer Ampatuan District, complete enumeration was used for both teachers and schools. Survey questionnaires comprised profiles of teachers and students-respondents, multi-grade teaching questionnaire administrators’ competencies, teachers’ competence, students’ experience, community support and participation, instructional adequacy of resources, and content management. Results showed consistent performance across the teachers, with only minimal variability in their COT ratings. The teachers met high professional standards, contributing positively to student learning outcomes and classroom environments. There was a low positive correlation between multi-grade teaching and teachers’ performance. As multi-grade teaching increases, teachers’ performance also tends to increase slightly. There was a low positive correlation between multi-grade teaching and student performance. As multi-grade teaching increases, students ‘performance tends to increase slightly. Thus, there was no significant relationship between ethnicity and students’ performance.